Resepsi al-Qur’an di Media Sosial (Studi Kasus Film Ghibah dalam Kanal Youtube Film Maker Muslim) - Fahrudin, Fahrudin (Program Studi Ilmu Al-Qur`an dan Tafsir, Fakultas Ushuluddin, UIN Sunan Kudus, 2020)
Al-Qur'an reception does not only occur in the offline world. It also happens in the online world, especially in the social media space. This paper intends to conduct a study of the reception of the al-Qur’an on social media, especially related to the film Ghibah that aired on YouTube. This research uses reception theory and idea transformation, this paper will reveal how the Qur'an receptions and the transformation of the unfortunate ideas contained in the film. The results of this study are the first, three groups of scenes in the film Ghibah receptive to three pieces of verse 12 of Surah al-Hujurat, namely believers are forbidden from gossiping, eating the meat of the gossiped and pious. The film is then received a hegemonic reception by viewers who agree and accept the contents of the message conveyed. Secondly, the idea of gossip when it is published in the film experiences shrinking and summarizing from those contained in the books of interpretation. The scenes that appear and the text that appears in the middle of the film become an important factor in the transformation.